2016
DOI: 10.1158/1078-0432.ccr-15-1701
|View full text |Cite
|
Sign up to set email alerts
|

Trop-2 Induces Tumor Growth Through AKT and Determines Sensitivity to AKT Inhibitors

Abstract: Purpose: Inhibition of AKT is a key target area for personalized cancer medicine. However, predictive markers of response to AKT inhibitors are lacking. Correspondingly, the AKT-dependent chain of command for tumor growth, which will mediate AKTdependent therapeutic responses, remains unclear.Experimental Design: Proteomic profiling was utilized to identify nodal hubs of the Trop-2 cancer growth-driving network. Kinase-specific inhibitors were used to dissect Trop-2-dependent from Trop-2-independent pathways. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Notably, though, our findings indicated that TROP2 has a vast negative prognostic impact on LUAD, but only a marginal one on LUSC, where Trop-2 expression associates to terminal differentiation to cornified cells [ 11 ], with formation of keratin pearls (Figure 1A ). Parallel findings were obtained for TP63 , which we had previously shown to be both an upstream driver of Trop-2 [ 8 , 9 ] and a downstream effector [ 12 ]. TP63 is a powerful diagnostic discriminant [ 13 ], and a cancer prognostic [ 14 ] and predictive [ 15 ] factor.…”
Section: Resultssupporting
confidence: 80%
“…Notably, though, our findings indicated that TROP2 has a vast negative prognostic impact on LUAD, but only a marginal one on LUSC, where Trop-2 expression associates to terminal differentiation to cornified cells [ 11 ], with formation of keratin pearls (Figure 1A ). Parallel findings were obtained for TP63 , which we had previously shown to be both an upstream driver of Trop-2 [ 8 , 9 ] and a downstream effector [ 12 ]. TP63 is a powerful diagnostic discriminant [ 13 ], and a cancer prognostic [ 14 ] and predictive [ 15 ] factor.…”
Section: Resultssupporting
confidence: 80%
“…By contrast, numerous studies reported activation of Akt kinase by Trop2, mostly in cancer cell lines [ 54 , 55 , 56 , 57 , 58 ] but also in murine mesenchymal stem cells [ 26 ]. A large proteomic analysis recently identified more than 100 signaling molecules modulated by Trop2, with PTEN/PIK3CA/Akt/GSK3ß being a major activated pathway in cancer cells [ 59 ].…”
Section: Trop2 In Healthy Tissue and Developmentmentioning
confidence: 99%
“…Despite the fact that Trop2 is considered a transmembrane protein, it can also be localized in the cytoplasm with possible functional consequences [ 42 , 65 , 76 ]. Cytoplasmic, but not membrane-bound Trop2, expression positively correlates with phospho-Akt in breast cancer specimens [ 59 ]. Stoyanova et al reported that Trop2 undergoes regulated intramembrane proteolysis (RIP) [ 67 ].…”
Section: Trop2 In Healthy Tissue and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It induces intracellular calcium release and activates the MAPK and Akt signaling pathways, thus implementing cell growth and EMT. 66,67 Its anti-adhesive activity boosts the migratory phenotype. 68 Trop-2 is a marker of cell stemness and is present in many normal tissues.…”
Section: Puzzling Expression Of the Trophoblast Cell Surface Antigen mentioning
confidence: 99%